Does Foreign Entry Spur Innovation? - Yuriy Gorodnichenko; Jan Svejnar; Katherine Terrell (Institute for the Study of Labor (IZA), 2015)
Our estimates, based on large firm-level and industry-level data sets from eighteen countries, suggest that FDI and trade have strong positive spillover effects on product and technology innovation by domestic firms in emerging markets. The FDI effect is more pronounced for firms from advanced economies. Moreover, our results indicate that the spillover effects can be detected with micro data at the firm-level, but that using linkage variables computed from input-output tables at the industry level yields much weaker, and usually insignificant, estimated effects. These patterns are consistent with spillover effects being rather proximate and localized.
Keywords: F23; M16; O16; P23; 330; innovation; FDI; spillovers; horizontal and vertical linkages; emerging markets; foreign competition